Productivity of Purse Seine Fishing Gear at PPP Labuan, Pandeglang Regency: English - Muhammad Andhika Wibawa Hermawan; Agung Setyo Sasongko; Yulda (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2025)
This research intends to assess the productivity rate of the Purse Seine fishing method at the Coastal Fishing Port (PPP) Labuan in Pandeglang Regency and to develop sustainable management approaches. A quantitative descriptive approach was used to evaluate productivity through indicators like Catch Per Unit Effort (CPUE) and Maximum Sustainable Yield (MSY). Data were obtained through observations in the field, interviews with fishermen, and recording of catches in February 2024 by the marine and fisheries office in Labuan. The results showed a decrease in CPUE from 219.11 kg/trip. The CPUE results show that Purse Seine productivity in Labuan can be said to be good, but if it continues to be left unchecked it will result in a significant decrease in certain species such as tuna and squid obtained from data released from the Labuan marine and fisheries office. Therefore, there must be steps to prevent fluctuations in the Labuan fishing sector by applying an ecosystem-based approach (EAFM) to maintain the sustainability of the marine ecosystem in the Sunda Strait.